O uso político do discurso de ódio no Brasil : um estudo de caso no Facebook (2016-2017) - Lemos, Joelma Galvão de (2018)
Hate as well as love are part of the psychic process of subjectivation of the individual and are found in the affective bonds that he establishes throughout his life, as well as in his social relations. The expression of affections and the ways in which they are structured can vary according to the socio-historical moment in which the subject lives and can cause changes in this social environment, by making possible new ways of social relations, as well as may suffer the influences of this medium. At certain moments, especially in situations of political and ideological disputes, it is possible to perceive the prevalence of one feeling in relation to another, as well as the political use of affections. Through the case study, we analyzed some hate speech posted on Facebook during the period of the impeachment of President Dilma Rousseff in 2016; in some posts that featured scenes of violence and barbarism, and postings in which browsers announced the exclusion of some friends who did not agree with their political position. The hate speech in the country is used politically in order to oppress and exploit, but it is possible to act a other discourse of hate as a means of denunciation, as a way to stop situations of injustice.